Pendampingan Pembuatan Formula Krim Lulur Scrub Beras Putih dengan Kalkulator Jamu di Paguyuban Jamu Gendong Tresno Asih, Depok Jawa Barat: Assistance in Producing White Rice Scrub Cream Formula using Herbal Calculators at the Paguyuban Jamu Tresno Asih, Depok, West Java - Ika Maruya Kusuma; Taufik Hidayat; Mohammad Fadhli Abdillah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Paguyuban Jamu Tresno Asih is one of the traditional herbal medicine communities in Depok, West Java. However, over time the number of members has decreased, this is due to a decrease in the interest of members of the Paguyuban Jamu Tresno Asih to produce and sell herbal medicine. The purpose of this partnership is to assist herbal sellers in making white rice scrubs with a herbal calculator which aims to increase the variety of products. The activities carried out include preparation, counseling and workshops on herbal calculators and making white rice scrubs and evaluations. The results of the evaluation of this activity showed that the white rice scrub cream with a herbal calculator it was easy to understand and the results of the organoleptic scrubs produced showed suitability. The increase percentage value of each understanding obtained for the function of the scrub cream is 63.63%; understanding of the ingredients of scrub cream 59.09%; understanding of the meaning and process of making scrub cream 36.37% and 31.82%. The herbal medicine seller at the Paguyuban Jamu Tresno Asih are interested in producing and selling white rice scrub cream as a product variation.